Elsa DORLIN - Se défendre - Une philosophie de la violence - UPOP Marseille (2020)
Se défendre. Une philosophie de la violence Conférence d’Elsa DORLIN En 1685, le Code noir défendait « aux esclaves de porter aucune arme offensive ni de gros bâtons » sous peine de fouet. Au XIXe siècle, en Algérie, l’État colonial interdisait les armes aux indigènes, tout en accordant aux colons le droit de s’armer. Aujourd’hui, certaines vies comptent si peu que l’on peut tirer dans le dos d’un adolescent noir au prétexte qu’il était « menaçant ». Une ligne de partage oppose historiquement les corps « dignes d’être défendus » à ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce « désarmement » organisé des subalternes pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Des résistances esclaves au ju-jitsu des suffragistes, de l’insurrection du ghetto de Varsovie aux Black Panthers ou aux patrouilles queer, Elsa Dorlin retrace une généalogie de l’autodéfense politique. Sous l’histoire officielle de la légitime défense affleurent des « éthiques martiales de soi », pratiques ensevelies où le fait de se défendre en attaquant apparaît comme la condition de possibilité de sa survie comme de son devenir politique. Cette histoire de la violence éclaire la définition même de la subjectivité moderne, telle qu’elle est pensée dans et par les politiques de sécurité contemporaines, et implique une relecture critique de la philosophie politique, où Hobbes et Locke côtoient Frantz Fanon, Michel Foucault, Malcolm X, June Jordan ou Judith Butler.
Keywords: antiracisme; approches et analyses; cours; discipline; militance; patriarcat; philosophie; pol5480; premier cycle; racisme; ressource en ligne; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap